2019
DOI: 10.1002/mrm.28088
|View full text |Cite
|
Sign up to set email alerts
|

Interleaved 31P MRS/1H ASL for analysis of metabolic and functional heterogeneity along human lower leg muscles at 7T

Abstract: Purpose MR offers the unique possibility to noninvasively investigate cellular energy metabolism via 31P MRS, while blood perfusion, which provides oxygen and substrates to the tissue, is accessible by arterial spin labeling (ASL) 1H MRI. Because metabolic and hemodynamic parameters are linked, it would be desirable to study them simultaneously. A 3D‐resolved method is presented that allows such measurements with high spatiotemporal resolution and has the potential to discern differences along an exercising mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(57 citation statements)
references
References 46 publications
5
51
1
Order By: Relevance
“…Intramuscular differences in k PCr have also been observed in the gastrocnemius muscle (Niess et al . 2020). In contrast to our study, PCr recovery after exercise was faster distally than proximally and the difference was much smaller (1.25 min −1 vs .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intramuscular differences in k PCr have also been observed in the gastrocnemius muscle (Niess et al . 2020). In contrast to our study, PCr recovery after exercise was faster distally than proximally and the difference was much smaller (1.25 min −1 vs .…”
Section: Discussionmentioning
confidence: 99%
“…2010; Niess et al . 2020). This is reflected in larger NIRS changes (deoxygenation) in the distal part of the vastus lateralis and gastrocnemius (Miura et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our maximum TE affected T 2 * quantification with a maximum error <4%, which was validated in phantom experiment. Also, some recent works showed that muscle metabolic and oxidative capacity varies along the length of the muscle even within the same muscle group 39 , which was also observed as a gradient in T 2 * weighted signals between two distal slice locations following exercise 23 . This suggests that even though the T 2 * slice should have similar kind of T 2 * response as the perfusion slice, but there might still be a gradient between the actual numbers.…”
Section: Discussionmentioning
confidence: 91%
“…This pulse sequence and exercise protocol provides a unique ability to investigate different aspects of muscle metabolic function (i.e., regional perfusion and tissue blood oxygenation). Although some studies reported simultaneous measurement of perfusion and T 2 * weighted signal at 7T 22,23 , but none of them measured quantitative T 2 *. T 2 * weighted signal, which can also be termed as BOLD signal 24,25 , is dependent on the change in T 2 * as well as the initial signal intensity, which is influenced by parameters such as inflow, baseline drifts and changes in T 1 25 .…”
Section: Discussionmentioning
confidence: 99%